Relationship between self-efficacy, task value, self-regulation strategies and active procrastination among pre-service teachers in colleges of education - Taura, Ali Abdullahi; Abdullah, Maria Chong; Roslan, Samsilah; Omar, Zoharah (Academic Journals, 2015)
This study examined the relationship between self-efficacy, task value, self-regulation and active procrastination of pre-service teachers enrolled in the colleges of education in Northern-western Nigeria. Samples of the study consist of 426 (223 males, 203 females) pre-service teachers with a mean age of 22.12 years. A descriptive correlation research design was employed to address the research objectives. Two research instruments were utilized to obtain the research data. Active Procrastination Scale (APS) was used to assess respondents’ level of procrastination, while the Motivated Strategies for Learning Questionnaire (MSLQ) was used to measure the level of their self-efficacy, task value beliefs, and self-regulation strategies. Pearson correlation and structural equation modelling (SEM) were performed to determine the relationship between the research variables. Findings indicated that all the variables of the study were significantly correlated. Furthermore, mediation analysis using SEM showed that there were indirect effects of self-efficacy and task value beliefs on active procrastination through self-regulation strategies as mediator. Recommendations in addition to the theoretical and practical implications of the study have been offered.